KEANEKARAGAMAN DAN POLA DISTRIBUSI GASTROPODA MANGROVE DI TELUK PANGPANG BLOK JATI PAPAK TN ALAS PURWO BANYUWANGI - Lina Susanti; Fuad Ardiyansayh; Hasyim As'ari (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2021)
The gastropods diversity have a role towards stability ecosystem in trophic level. The existence gastropods really take effect for other organism the trophic level higher than gastropods. The purpose of was to determine the value of diverity and distribution patterns of gastropods in the mangrove forest, Jati Papak Block National Park Alas Purwo. The method used in this research is by using purposive sampling method. Sampling was divided into three stations with a range of 250 m from each station.Each station is 220 m of long and 96 m of wide with a plot measuring 2 × 2 m2. The result obtained 8 families of Gastropods with 13 genus and 19 species. Gastropods diversity ranges from H`=1.387-1.359 which indicates that the area has a moderate diversity value. The distribution pattern of gastropods between location has two distribution patterns, namely clustered and random distribution patterns